EFEKTIFITAS PENGARUH JUMLAH UMK DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJADI INDONESIA - Muammar Fazri Ramadhan; Reza Juanda (Jurnal Ekonomi Regional Unimal, 2021)
This study analyzed the effect of the number of Micro and Small Enterprises and the minimum wage on employment in Indonesia. This study used secondary data in the form of data on the number of workers in micro and small enterprises, the number of micro and small business units, and minimum wage data for three years (2017, 2018, and 2019) in Indonesia taken from the Central Bureau of Statistics. The data analysis method used is the panel data regression method with the help of Eviews. The results partially showed that the number of Micro and Small Enterprises significantly influenced employment in Indonesia, and y, the minimum wage did not significantly influence employment in Indonesia. Simultaneously, the number of Micro and Small Enterprises and the minimum significantly influenced employment in Indonesia.